Clinical outcomes after elective double-embryo transfer in frozen cycles for women of advanced maternal age: A retrospective cohort study. Issue 9 (4th March 2022) - Wang, Zilian; Zhu, Haiyan; Tong, Xiaomei; Jiang, Lingying; Wei, Qun; Zhang, Songying
Abstract : Abstract: We aimed to determine the clinical outcome of double cleavage-stage embryo transfers in frozen-thawed embryo transfer cycles for older women. This study analyzed a total of 8189 cleavage-stage frozen-thawed embryo transfer cycles between January 2013 and December 2017 at Sir Run Run Shaw Hospital. All cycles were sorted into 3 groups based on patient age: ⩽35 years (Group A), 36 to 37 years (Group B), and ≥38 years (Group C). The clinical pregnancy rate (CPR), implantation rate (IR), live birth rate (LBR), miscarriage rate, multiple pregnancy rate (MPR), preterm birth rate, and low-birth-weight rate were compared between the 3 groups. Significant differences in CPR, IR, LBR, MPR, and premature birth rate were found among the 3 groups. The CPR, IR, LBR, and MPR in Group A were higher than those in Group C. Transfers of 2 high-quality embryos resulted in significant differences in CPR, IR, LBR, MPR, and neonatal weight among the 3 groups, but no differences in premature birth and abortion rates were observed. Transfers with 1 high-quality and 1 fair-quality embryo resulted in significant differences in CPR, IR, and LBR among the 3 groups. Comparison of transfers of 2 high-quality embryos with 1 high-quality and 1 fair-quality embryo showed that the CPR and LBR were significantly lower for the latter in Groups A and C, but Group B had no salient changes. Higher IR and LBR and lower MPR may be achieved by selection of optimal embryo types for patients of different ages. Two high-quality embryos need to be transferred in women older than 38 years. For women aged 36 to 37 years, 1 high-quality embryo or 1 high-quality plus 1 fair-quality embryo should be singled out for transfer. For women younger than 35 years, a single high-quality embryo should be selected for transfer.